MODEL DISCREPANCY SEBAGAI EVALUASI PROGRAM PENDIDIKAN - Nor Fadhilah; Asmanah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
Programs designed to advance education continue to progress and develop dynamically. Improving the program requires an evaluation process. There are various evaluation models used in improving educational programs depending on the aspects needed for improvement or refinement. The purpose of this research is to discuss the basic concepts of the discrepancy model evaluation made by Provus. This research is a library study with data obtained through the study of relevant books and articles and then analyzed using a qualitative approach consisting of: (1) data reduction, (2) data display, and (3) drawing conclusions. Evaluation The discrepancy model is one type of appropriate approach in evaluating an educational and learning program. The procedures used in the discrepancy evaluation are (1) design, (2) installation, (3) process, (4) product, and (5) comparison or the fifth in the form of costs and benefits if needed. The result of the discrepancy model evaluation is knowing the gap between the expected conditions and the reality on the ground, so that it can be a guide for the next step in making decisions.